Response Time analysis for Apache Web server versions based on 32 or 64 bit Architecture - Hama Ali A Faraj, Kamaran; Nawzad Ahmad, Tara; Othman Sharif, Hawar; Rasul, Pshko (International Journal of Computer Sciences and Engineering, 2025)
response time (RT) has a significant feature in both of traditionally response time (TRT) with physical (face-to-face) Businesses, and Automated response time (ART) with web-based businesses. The TRT is very primitive in physical (face-to-face) business and depended on human activity with devices reliability as well. TRT is very changeable from one person to another person and very complicate to calculate results of response time analysis due to that the TRT very manually and far from using of modern technologies. Nevertheless in ART the response time depended on web technology components, one of the web technology components is software web server that is between frontend (presentation) and backend (database). Web server in any ART by Web-based response time (WRT) is more advanced than TRT. The example of open source web server is apache web server. In this paper the evaluation of response time for different versions of apache web servers which is compatibility with different PhpMyadmin-EasyPhp. Thus, each version of Easyphp is with different version of Apache, Mysql, Php (AMP). The versions of apache web servers which tested are: 1) EasyPhp1.7 with apache 1.3.27, 2) EasyPhp1.8 with apache1.3.33, 3) EasyPhp3 with apache 2.2.11 4) EasyPhp5.6.3.0 with apache 1.3.27, and 5) EasyPhp12.1 with apache 2.4.2. All those versions of apache web server will be test it by simple search engine for Page Generated in Seconds with 32-bit computer Architecture and 64-bits computer Architecture. Web server is one of the mostly important tiered architecture in web technology components that communicate between client side and server side. There are plenty of different versions of web servers with Phpmyadmin-Easyphp. In this paper, the response time of the best apache web server will be found out over either computer architecture 32-bit or 64-bit. Finally the relation between computer architecture and internet architecture became one of our aims. The only suitable methodology for this paper that related and followed is the waterfall model because it’s appropriate than the other methodologies.